Kesejahteraan Sosial Perspektif Al-Qur`an - Ismail, Asep Usman (Social Welfare Study Program, 2015)
The Qur’an uses some terms that meaningful social welfare. Among the terms that the coverage meaning breadth and depth, and describes the concept of social welfare is fundamentally, the term, al-Falah which giving to al-muflihûn, prosperous society on the basis of faith and piety, the ultimate goal of human life in this world. There are five pillars of social welfare includes health, education, housing, and social security. One of very important aspect of welfare problems studied social work is poverty. The results of the study authors point out that Al-Qur`an mentions the term poor in the form 11 times and call it in the plural, masâkîn, as many as 12 times. So, overall Al-Qur`an mentions the term poor as much as 23 times. Al-dha’îf causes of poverty, weak spirit, reason and science weak, physically weak, and the weak skills of Al-khawf, i.e not dare to take the risk of failure, loss, or a loss of capital. Al-Kaslan, namely the state of one’s soul is overwhelmed by laziness Al-grabber, the state of a person who is dominated by the miserly nature. This poverty of cause of other social welfare issues such trafficking. How to cope with the strengthening of the family as a form of social welfare development.Keywords: Lima Pilar, Kesejahteraan Sosial, Kemiskinan, dan Penguatan Keluarga.